Variations in the course and branching pattern of musculocutaneous nerve - A Amar Jayanthi; K G Arunkumar (Wolters Kluwer Medknow Publications, 2013)
Background and aim: The variations in the course and communicating branches of musculocutaneous nerve is of clinical importance in the treatment of recurrent compression neuropathies and in the diagnosis of median nerve lesions. Most of the reports on anatomical variations of musculocutaneous nerve are single case studies and such studies with emphasis on gender difference in a sample of Keralite population are rarely reported. The objective of the present study is to observe the variations in the course of musculocutaneous nerve with special reference to communications with other nerves of the arm and to study the correlation between gender and variations of the nerve. Materials and Methods: Two hundred and sixty four arms were dissected in the department of Anatomy, Government medical college, Thrissur and studied for variations of muculocutaneous nerve. Analysis was done with epi info, using proportions, confidence interval and Chi Square test. The communications noted were classified using the available classifications of Le Minor, Venieratos and Anagnostopoulou and Choi et al. Results: Nerve variations were seen in 24.2 % cases which include, absence of the nerve (3.4%), nerve not piercing coracobrachialis (12.4%) and communication to median nerve (15.1%). All the variations observed were statistically not significant. The embryological basis for the axonal pathfinding is considered as a result of both guidance molecules and electrical activity that change the calcium homeostasis within the growth cone to regulate growth cone turning. Conclusion: Variations that were observed in the present study may give sufficient and relevant data on the nerves, among Keralite population in which studies are few.